The Application Of Data Mining To Find Out The Level Of Poverty In Padang Kuas Village Using The K-Means Clustering Method - Lili Purnama Sari; Maryaningsih Maryaningsih; Lena Elfianty (Jurnal Media Computer Science, 2026)
Poverty is one of the complex social problems and is the main focus of development in many areas that affect various aspects of people's lives, especially in rural areas. Padang Kuas Village is one of the villages in Seluma Regency in Bengkulu Province. Based on test data of 88 residents of Padang Kuas Village in 2023, the results of the Cluster C1 data grouping (very poor group) consisting of 27 population data, Cluster C2 (poor group) consisting of 36 population data, Cluster C3 (almost poor group) consisting of 1 population data, and Cluster C4 (vulnerable poor group) consisting of 24 population data. Based on the system testing that has been carried out, it can be concluded that the Village Office can find out the level of poverty which has been divided into 4 groups, and the application is quite helpful in identifying residents who fall into groups according to the level of poverty.